USING HERBARIUM RECORDS AND IUCN RED LIST TO UNRAVEL EXTINCTION RISK PATTERN IN GENUS GARCINIA IN NIGERIA (FULafia Journal of Science and Technology, 2025)
Trees of economic importance are many times vulnerable to extinction due to factors such as anthropogenic pressure, ethnobotanical uses, urbanization, climate change and spread of invasive species. Species in genus Garcinia are well known for their ecological and economic importance. In this study, herbarium records from the Forest Research Institute of Nigeria (FRIN) national herbarium were searched to determine the distribution of species of Genus Cola in Nigeria. The herbarium spreadsheet also contain information regarding their habitat type records. This records were used in generating species distribution map and analyze the habitat type. The IUCN (International Union of Conservation of Nature) Red List web platform was used to determine the conservation status and threats to species of Garcinia found in Nigeria. This study revealed that Garcinia is highly distributed in Cross River state in Nigeria than other parts of the country. This study revealed that Garcinia is a threatened genus in Nigeria. Some species of Garcinia has not been evaluated for conservation purpose. This study conclude that Garcinia might be at the verge of complete extinction if there are no conservation interventions for the species. It is recommended that species of Garcinia in Nigeria be regenerated to prevent their extirpation and also a recent local population assessments of all the species in this genus should be encouraged.
Keywords: Biodiversity; Biogeography; Conservation; Ecosystem ecology; Taxonomy